A happier life ebook - Woodson Harvey, Kristy (2024)
" New York Times bestselling author and southern sensation Kristy Woodson Harvey" ( Good Morning America ) presents a touching novel about eternal love and the places we call home. The historic houses in the seaside town of Beaufort, North Carolina, have held the secrets of their inhabitants for centuries. One of the most enduring refuses to be washed away by the tide: What happened to Rebecca and Townsend Saint James on that fateful night of their disappearance in 1976? Now, the granddaughter they never knew, Keaton Smith, is desperate for a fresh start. So when her mother needs someone to put her childhood home in Beaufort on the market, she jumps at the chance to head south. But the moment she steps foot inside the abandoned house, which has been closed for nearly fifty years, she wonders if she's bitten off more than she can chew. Wading through the detritus of her grandparents' lives, Keaton finds herself enchanted by their southern traditions—and their great, big love. As she gets to know her charming next-door neighbor, his precocious ten-year-old son, and a flock of endearingly feisty town busybodies, Keaton begins to wonder if the stories she has been told about her grandparents are true. Keaton's grandmother, Rebecca "Becks" Saint James's annual summer suppers are the stuff of legend, and locals and out-of-towners alike clamor for an invitation to her stunning historic home. But, in the summer of 1976, she's struggling behind the facade of the woman who can do it all—and facing a problem that even she can't solve. As Keaton and Becks face new challenges and chapters, they are connected through time by the house on Sunset Lane, which has protected the secrets, hopes, and dreams of their family for generations. "The novel to read this year" (Annabel Monaghan) explores the power of family, the boundless nature of love, and the idea that discovering where we came from just might lead us to A Happier Life.